TATA CARA PEMUNGUTAN PAJAK PENGHASILAN (PPH) PASAL 22 DAN PAJAK PERTAMBAHAN NILAI (PPN) ATAS BELANJA BARANG PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA BANJARMASIN - Jody Aptriady; Naimatul Aufa (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
The research in this final project aims at the procedures for collecting PPh 22 and VAT on goods + expenditures carried out by government agencies and then reviewing from books, references and data obtained to make suggestions and conclusions based on - the results of the analysis to -more -increase--return- compliance in collecting pph 22-and-vat. The conclusion of this study is: the collection of PPh 22-and-VAT is carried out by the government treasurer properly according to the applicable laws and regulations by using a holding system.